The little book of cases in hospitality management : Stories from industry practitioners - Tesone, D.V.; Ricci, Peter (New Jersey : Pearson/Prentice Hall, 2006)
"The Little Book of Cases in Hospitality Management: Stories from Industry Practitioners provides students of Hospitality Management with forty-five case studies concerning lodging, foodservice, theme parks, attractions, resorts, recreation, events, transportation, and entertainment. Each of the cases in this book is taken from the real-life experiences of managers working in the hospitality industry."
I. MICRO CASES FOR MANAGEMENT STRATEGIES. 1. Productivity Enhancement. 2. Leading a Turnaround Strategy. 3. Value-added Restaurant Service. 4. Training Strategies. 5. Turnaround Strategies and Employee Relations. 6. Rules and Progressive Discipline. 7. A New Management Assignment. 8. Dealing with Problem Employees. II. CASE VIGNETTES IN MANAGEMENT & SUPERVISION. 9. The Restaurant. 10. Career Paths. 11. A Comparison of Management Styles. 12. Management and Employee Motivation. 13. The Department Transfer. 14. The Training Scenario. 15. Manager's Reputations. 16. Coaching, Counseling, and Discipline. 17. The Special Restaurant. 18. Subjective Management Practices. 19. Job Opportunities. III. CASE VIGNETTES IN HUMAN RESOURCE MANAGEMENT. 20. Human Resource Management Overview. 21. Recruitment and Retention. 22. Employee Productivity and Value-Added Management. 23. Legal Compliance. 24. Employee Relations and Retention. 25. Employee Retention. 26. Legal Compliance. 27. Recruitment and Selection. 28. Employee Training and Needs Assessment. 29. Employee Compensation. 30. Performance Appraisals and Management Responsibility. 31. Management Communications and Employee Relations. 32. Leadership Development. 33. Employee Motivation and Recognition Programs. 34. Starting and Running an HR Office. IV. HOSPITALITY OPERATIONS CASES. 35. The Invisible Car. 36. Taking Care of the Elderly. 37. There's a Mouse in the House. 38. Forty-Eight Hours. 39. Don't Park Here. 40. The Confused Consultant. 41. Can You Float Me a Loan? 42. The "Sick" Van. 43. The Prejudice Housekeeper. 44. The Overnight "Vigil." 45. The Disappearing Dodge.
Keywords: HOSPITALITY INDUSTRY -- MANAGEMENT -- CASE STUDIES